High-flow nasal oxygen is the reference treatment in acute hypoxemic respiratory failure: Pro - Jean-Pierre Frat; Sylvain Le Pape (Journal of Intensive Medicine, 2025)
In patients with hypoxemic acute respiratory failure (ARF), the first-line treatment is oxygen therapy, which may include the administration of high-flow nasal oxygen (HFNO), noninvasive ventilation (NIV), or continuous positive airway pressure (CPAP). In addition to improving oxygenation, HFNO and NIV reduce the work of breathing as compared to standard oxygen, while CPAP does not. However, tolerance to NIV and CPAP is clinically challenging, resulting in treatment interruption in 10 %–20 % of cases. Compared to standard oxygen, HFNO has been shown to reduce the risk of intubation, while the benefits of NIV or CPAP, even when delivered via a helmet, require further evaluation. Although evidence for the efficacy of HFNO in reducing mortality remains inconclusive, HFNO has emerged as the reference treatment and is recommended for patients with hypoxemic ARF given its benefit in reducing the risk of intubation.